The potential of social networking sites in inpatriate adjustment - Pekonen, Tytti (My University, 2013)
People make up one of the most important resources for a corporation and therefore it has to continuously seek an ever more diverse and international workforce. Inpatriation is another way of utilizing foreign expertise in a corporation. An inpatriate refers to a person that is on an international assignment at the headquarters of a corporation, where they have been sent either from a subsidiary abroad or from a third country outside the corporation. Strengthening the social network of the inpatriate and their family contributes to the adjustment process and furthermore the success of the work assignment. As social networking sites are currently the fastest developing personal networking tools in the world, it is interesting to see how they can help in inpatriate adjustment. The objective of this thesis is to explore the potential of social networking sites (SNS) in inpatriate adjustment. The main objective can be divided into three sub objectives: 1. What is SNS used for during the inpatriate assignment? 2. What are the inpatriates’ motivations to use SNS? 3. Could the three facets of adjustment (work, interaction and general) be gained through SNS? This qualitative study utilizes the theme interview data collection method and the thematic analysis approach for analysing the interview data. From the interviews with five Indian inpatriates in Finland the most mentioned uses of SNS were related to participating (sharing opinions, recommendations and discussing things and connecting to friends, family and colleagues) and consuming (collecting information for work and free time), the least mentioned use of SNS was producing (posting videos, photos and updates). An interesting finding was that the five interviewees did not use SNS for purely entertainment motives at all during their assignment. This thesis found that all three facets of adjustment could potentially be gained through SNS.